Penggunaan Susu Kedelai Sebagai Substitusi Susu Sapi Pada Pengolahan Es Krim Kelapa (Cocos Nucifera L.) - Bororing, Chrisel Elgreit; Oessoe, Yoakhim Y. E.; Ludong, Maya M. (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2023)
The purpose of this study was to analyze the effect of soy milk substitution on protein content, melting power and the level of consumer preference for coconut ice cream. This research was conducted experimentally using RAL (completely randomized design), with 5 treatments. The formulation of cow's milk and soy milk consisted of A (100%: 0%), B (75%: 25), C (50%: 50%), D (25%: 75%), E (0%: 100%) in 3 replications. The data obtained were analyzed using the analysis of variance method or ANOVA (Analysis of Variant).